Effects of dietary CLA on n-3 HUFA score and N-acylethanolamides biosynthesis in the liver of obese Zucker rats. (July 2015) - Piras, Antonio; Carta, Gianfranca; Murru, Elisabetta; Lopes, Paula A.; Martins, Susana V.; Prates, José A.M.; Banni, Sebastiano
Abstract: We have recently shown that PPAR alpha agonists induce N -oleoylethanolamide (OEA) and N -palmitoylethanolamide (PEA) biosynthesis. Conjugated linoleic acid (CLA), a known dietary PPAR alpha inducer, may therefore increase OEA and PEA levels and favor docosahexaenoic acid (DHA) biosynthesis by enhancing peroxisomal β-oxidation via induction of liver PPARα. To evaluate whether CLA is able to increase DHA, OEA and PEA levels and thereby influencing liver lipid deposition in a model of visceral obesity-induced fatty liver, Zucker rats were fed a background diet rich in saturated fat with or without 1% of CLA for 4 weeks. Our data showed that CLA intake increased DHA, OEA and PEA levels in the liver by 24%, 31% and 36% respectively, and reduced hepatic lipid accumulation by 16%. We may conclude that dietary CLA is able to influence not only fatty acid metabolism but also the biosynthesis of bioactive mediators such as OEA and PEA which may contribute to ameliorate fatty liver.